Effectiveness of lineament analysis as a method for ore deposit exploration in the Greenstone belts of the southern Guiana Shield in the Amapá Region, Brazil (2022)
The lineament analysis method consists in the mapping in the lineaments of a given area. This method can be a good alternative to the traditional exploration methods, because it is considerably cheaper than these ones, because most of the time the data sources are open to the public. The main purpose of this method is to identify the zones with the highest density of lineaments, which can be the zones hosting ore deposits. This method can be performed using optical, radar remote sensing data, but also magnetic data, which makes this method more feasible, due to it is not limited to a certain type of data. Moreover, the results from the different data can change because each one of the type of data reflects different features of the zone. This study will analyze the relation between the density of lineament and the presence of ore deposits in the northwest of the city of Macapá in Brazil. In order to achieve this, magnetic and satellite data will be use to extract the lineaments of the area using the Arcgis pro software.The lineaments extracted from the sentinel 1 VV and VH polarization images resulted to be the ones that better located the known ore deposits of the study area. Also, the directional filtered image from the S1A VH polarization images made a good localization of the ore deposits of the study area and also enhance the lineaments.